2010
DOI: 10.1161/circresaha.110.231910
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Cardiac Fibroblasts

Abstract: Cardiac fibroblasts play a critical role in maintenance of normal cardiac function. They are indispensable for damage control and tissue remodeling on myocardial injury and principal mediators of pathological cardiac remodeling and fibrosis. Despite their manyfold functions, cardiac fibroblasts remain poorly characterized in molecular terms. Evidence is evolving that cardiac fibroblasts are a heterogeneous population and likely derive from various distinct tissue niches in health and disease. Here, we review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
190
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(194 citation statements)
references
References 75 publications
(91 reference statements)
1
190
0
1
Order By: Relevance
“…The EPDC produced by epicardial EMT are considered a major source of CF, 103 and several studies in avian 9,15,17,19 and mouse embryos 10,11,80 indicate that the embryonic epicardium is the first and main contributor of embryonic CF ( Figure 4B, C). Other sources of CF are the EMT that occurs in the embryo during the formation of cardiac cushions 104 or post-natally via the recruitment of circulating bone marrow cells.…”
Section: Epicardial Origin Of Cardiac Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPDC produced by epicardial EMT are considered a major source of CF, 103 and several studies in avian 9,15,17,19 and mouse embryos 10,11,80 indicate that the embryonic epicardium is the first and main contributor of embryonic CF ( Figure 4B, C). Other sources of CF are the EMT that occurs in the embryo during the formation of cardiac cushions 104 or post-natally via the recruitment of circulating bone marrow cells.…”
Section: Epicardial Origin Of Cardiac Fibroblastsmentioning
confidence: 99%
“…Nkx2.5-Cre-mediated myocardial deletion of ␤1-integrin corroborated this finding in vivo, resulting in weak myocardial proliferation, a thin compact layer at E14.5, and perinatal death. 107 The biomedical relevance of CF is enormous, 103 as is demonstrated by the massive fibrosis that follows myocardial infarction. The classic cardiac scar that appears in response to myocardial death is a growing tissue that progressively limits the biomechanical properties of the ventricles, ultimately causing heart failure.…”
Section: Epicardial Origin Of Cardiac Fibroblastsmentioning
confidence: 99%
“…3 Fibroblasts have been shown to derive from epicardial EMT during midgestation, although other developmental origins have not been excluded. 2 Using epicardial-specific Cre drivers, we observed that most, but not all, cardiac fibroblasts were of epicardial origin. We identified a second cardiac fibroblast lineage residing mainly in the septum that we show likely derives from endocardial EndoMT associated with endocardial cushion formation.…”
Section: 2mentioning
confidence: 92%
“…2 To label cardiac fibroblasts in heart at baseline, we used a Collagen1a1-GFP reporter line 4 that we found was not expressed in nonfibroblast lineages including endothelium, pericytes, and haematopoietic lineages. The mesenchymal marker PDGFRa, expressed by fibroblasts, 5 was coincident with Collagen1a1-GFP.…”
Section: 2mentioning
confidence: 99%
“…Granulation tissue comprises mostly macrophages and myofibroblasts, the latter being derived from a variety of sources including resident CF, endothelial cells, epithelial cells, bone marrow-derived fibrocytes, pericytes and smooth muscle cells (Krenning et al, 2010;Zeisberg and Kalluri, 2010). Myofibroblasts are a differentiated form of fibroblasts, characterised by increased alpha-smooth muscle actin (SMA) expression, that are not present in the normal healthy myocardium (Tomasek et al, 2002;van den Borne et al, 2010).…”
Section: Granulation Phasementioning
confidence: 99%